L’Hystoire romaine de la belle Cleriende de Macé de Villebresme, à la croisée de l’épître et de l’élégie - Marois, Laurence (Renaissance and Reformation / Renaissance et Réforme, 2011)
In 1529, and again in 1533, Lyon printer Claude Nourry published the epistle Lepistre de la belle Cleriende. Here we can trace—in this epistle by Macé de Villebresme—the influence of Ovid’s Heroides, translated into French around 1492 by Octovien de St Gelais. Using the definitions of the epistolary and elegiac genres established by the different poetic arts of the time, this article aims to present Lepistre de la belle Cleriende in the context of these literary genres and their development. Specifically, a comparison between the works of Ovid and Macé de Villebresme will allow a better understanding of the influence that the translation into French of the Heroides has had on the versified epistolary genre during the first half of the sixteenth century in France.